Asertywność jako istotna kompetencja społeczna w rzeczywistości szkolnej uczniów - Kaźmierska, Marlena (Kultura-Społeczeństwo-Edukacja, 2018)
The main aim o the article is to highlight the devolopment of assertiveness in students. The article presents concepts of social skills and assertiveness. In emphasizes the issue of non-assertive behaviour in education. Next the article describes the value of assertiveness skills to the life of the student and it presents to teachers methods for teaching assertiveness to children.